2007
DOI: 10.1134/s0006297907030078
|View full text |Cite
|
Sign up to set email alerts
|

Proteinase inhibitors from the tropical sea anemone Radianthus macrodactylus: Isolation and characteristic

Abstract: Two new serine proteinase inhibitors (RmIn I and RmIn II) from the tropical sea anemone Radianthus macrodactylus have been isolated and characterized. The purification procedure includes polychrome-1 hydrophobic chromatography, Superdex Peptide 10/30 FPLC, and Nucleosil C(18) reverse-phase HPLC. The molecular masses of RmIn I, RmIn II, and the complexes RmIn II/trypsin and RmIn I,II/alpha-chymotrypsin have been determined. The K(i) values of RmIn I and RmIn II for trypsin and alpha-chymotrypsin have been deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 20 publications
1
24
0
Order By: Relevance
“…1). The results of the computational evaluation of the secondary struc ture element content were close to the data obtained experimentally for those inhibitors studied in vitro previously [3,21,45].…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…1). The results of the computational evaluation of the secondary struc ture element content were close to the data obtained experimentally for those inhibitors studied in vitro previously [3,21,45].…”
Section: Resultssupporting
confidence: 78%
“…Interestingly, many of the sea anemone polypeptides of Kunitz fold may exhibit various functionalities, in other words, they are poly functional. For example, in addition to serine protease inhibitory activity [3,4,[11][12][13][14][15][16][17][18], they are capable of inhibiting asparagine and cysteine proteases [3,4], blockage of potassium channels Kv1.1 and Kv1.3 [19,20], and antihistamine activity [21].…”
mentioning
confidence: 99%
“…To date, a number of highly homologous native serine protease inhibitors has been isolated from different species: Anemonia sulcata [7,13], Heteractis crispa [14,15,16,17,18], Anthopleura aff. xanthogrammica [19,20], Anthopleura fuscoviridis [21], Stichodactyla helianthus [22,23,24], and Stichodactyla haddoni [8].…”
Section: Introductionmentioning
confidence: 99%
“…The HCGS peptide subfamily and their evolutionary relationships were described in details previously [11,25]. Two sea anemone trypsin inhibitors, RmInI and RmInII, possess antihistamine activity in vivo [15]. Recently, we have shown that rHCGS1.20 has an anti-inflammatory activity thanks to its ability to reduce the content of nitric oxide (NO) in lipopolysaccharide activated macrophages.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the separation of the peptide pool from the sea anemone secretion has been done by gel filtration in Sephadex G-50. Nonetheless, other gel filtration media (FPLC and HPLC) are suitable such as Superdex Peptide [67] and Superdex 30 [68][69][70], which provide faster separations, higher resolution and appropriate selectivity for fractionating the 1-10 kDa peptides. The column can be calibrated by using molecular weight standards as described by Lagos [27] (a similar procedure was used in the present work) or by SDS-PAGE analysis of eluting fractions [28].…”
Section: Unifying Strategies For the Analyses Of Sea Anemone Secretionmentioning
confidence: 99%